Application of Self-prepared AFB Stain Kit in Forensic Medicine for Tuberculosis Diagnosis - Siriwattanarat, Ruthairat; Chaimad, Yasudama (Science Essence Journal, 2024)
Tuberculosis (TB), a highly contagious and severe disease, is caused by Mycobacterium tuberculosis of the Acid Fast Bacillus (AFB). During autopsies, bodies suspected of being infected with Tuberculosis will have lung biopsies taken and sent for examination at the forensic histopathology laboratory. The Ziehl-Neelsen (ZN) staining technique is used to diagnose TB from tissue slides; however, it is not commonly used in the workflow of forensic histopathology laboratories. Consequently, when tissue samples are dispatched for TB diagnosis, it requires analysis at an external agency. This incurs supplementary expenses and extends the time for result reporting. In this research, we prepared a self-prepared AFB stain kit for AFB stain following the ZN staining technique, but modified it without heating in the lung tissue slide staining step. Our objective was to compare the diagnostic efficacy of self-prepared AFB stain kit with the conventional AFB stain kit. The effectiveness of both AFB stain kits was assessed by three experts. All data were analyzed by covariance (ANCOVA). The P value is more than 0.05, which is considered not statistically significant for all various aspects that have been examined. This indicates that both AFB stain kits, without heating in the staining step, showed no difference in the results and can be used for TB diagnosis in forensic histopathology laboratories.